2004
DOI: 10.1136/bmj.328.7444.879
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of antidepressants for children and adolescents

Abstract: How safe and effective are antidepressants in children and adolescents? The authors of this review have found disturbing shortcomings in the methods and reporting of trials of newer antidepressants in this patient group Antidepressants introduced since 1990, especially selective serotonin reuptake inhibitors and venlafaxine, have been used increasingly as first line treatment for depression in children. 1 2 The safety of prescribing antidepressants to children (including adolescents) has been the subject of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
157
0
16

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(173 citation statements)
references
References 20 publications
0
157
0
16
Order By: Relevance
“…Identification of such a biological marker of treatment response among pediatric patients would advance the field dramatically. As recent reviews have concluded, randomized controlled trials indicate that current treatments are effective for only a subset of youth with anxiety and mood disorders (40,41). Although symptom severity and the presence of comorbid disorders sometimes predict poorer outcomes (23), this is not always the case.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of such a biological marker of treatment response among pediatric patients would advance the field dramatically. As recent reviews have concluded, randomized controlled trials indicate that current treatments are effective for only a subset of youth with anxiety and mood disorders (40,41). Although symptom severity and the presence of comorbid disorders sometimes predict poorer outcomes (23), this is not always the case.…”
Section: Discussionmentioning
confidence: 99%
“…This review critiques the evidence of efficacy and safety available from published RCTs of SSRI or venlafaxine use in children and adolescents. It is important to note that, after this article was submitted for publication, Jureidini and others published a review with a nearly identical purpose (12). Their paper examines the identical list of articles but emphasizes different critiques of the research, some of which overlap with the discussion below.…”
Section: Rationalementioning
confidence: 99%
“…For example, consider the field of child psychiatry (Raz, 2006). On the one hand, pediatric antidepressant treatment carries an NNT between 3 and 10 (i.e., for every three to ten children administered antidepressants, only one will improve better than placebo), an NNH (e.g., in terms of suicidal ideation or suicide attempt) from 112 to 200 (Bridge et al, 2007), and a range of potentially severe side-effects (Jureidini, Doecke, Mansfield, Haby, & Menkes, 2004); pharmacological treatment of ADHD with atomoxetine carries an NNT of 3 for treatment response and 10 for relapse prevention, and an NNH of 9 for abdominal pain, 22 for vomiting, 30 for dyspepsia, and 19 for somnolence (Cheng, Chen, Ko, & Ng, 2007). On the other hand, EEGnf studies rarely report NNT or NNH, yet side-effects remain mild and uncommon (Hammond & Kirk, 2008), and positive outcomes appear to persist well beyond the treatment period (Gani, Birbaumer, & Strehl, 2008;Gevensleben et al, 2010;Leins et al, 2007;Strehl, Leins, et al, 2006).…”
Section: Placebo Science and Clinical Practice In The Context Of Eeg-nfmentioning
confidence: 99%